Polyanthraquinone as a Reliable Organic Electrode for Stable and Fast Lithium Storage. Issue 47 (28th September 2015) - Song, Zhiping; Qian, Yumin; Gordin, Mikhail L.; Tang, Duihai; Xu, Terrence; Otani, Minoru; Zhan, Hui; Zhou, Haoshen; Wang, Donghai
Abstract: In spite of recent progress, there is still a lack of reliable organic electrodes for Li storage with high comprehensive performance, especially in terms of long‐term cycling stability. Herein, we report an ideal polymer electrode based on anthraquinone, namely, polyanthraquinone (PAQ), or specifically, poly(1, 4‐anthraquinone) (P14AQ) and poly(1, 5‐anthraquinone) (P15AQ). As a lithium‐storage cathode, P14AQ showed exceptional performance, including reversible capacity almost equal to the theoretical value (260 mA h g −1 ; >257 mA h g −1 for AQ), a very small voltage gap between the charge and discharge curves (2.18–2.14=0.04 V), stable cycling performance (99.4 % capacity retention after 1000 cycles), and fast‐discharge/charge ability (release of 69 % of the low‐rate capacity or 64 % of the energy in just 2 min). Exploration of the structure–performance relationship between P14AQ and related materials also provided us with deeper understanding for the design of organic electrodes. Abstract : No compromises! An ideal polymer electrode based on anthraquinone, poly(1, 4‐anthraquinone) (P14AQ), was applied as a cathode for rechargeable lithium batteries (see picture). Unrivaled by other organic electrodes, it showed exceptional performance, including stable cycling (99.4 % capacity retention after 1000 cycles) and fast discharge/charge ability (releasing 69 % of the low‐rate capacity or 64 % of the energy in just 2 min).